THE PROMOTION AND DEVELOPMENT OF GREEN ECONOMY SURVEILLANCE CAPABILITIES IN COMMUNITIES THROUGH INNOVATIVE BIODIVERSITY KNOWLEDGE SETS - Phodong, Arpakron; Makerd, Watcharasak (Journal of MCU Nakhondhat, 2026)
The objectives of this research were: 1) To study and synthesize knowledge from biodiversity, 2) To develop training models and curricula, 3) To develop prototype innovators and volunteers, and 4) To develop participatory network management. This research was conducted using the Research and Development (R&D) method. Target group Participants from 15 districts, with 120 individuals trained and developed as prototype innovators and community volunteers. The independent variable was the biodiversity knowledge innovation and the training curriculum for enhancing community green economy monitoring competencies, while the dependent variable was the community green economy monitoring competency. The research instruments consisted of a field survey form for recording plant and animal species and ecosystem conditions, an interview guide for local wisdom experts, a focus group discussion record form, training curriculum and supporting instructional materials, and a competency test on community green economy monitoring. The research findings revealed the following: 1. Study and Synthesis of Knowledge: The study of biodiversity in Nakhon Sawan Province found that the community possesses outstanding natural capital, including ecosystems, diversity of local plant species, aquatic animals, and traditional wisdom in resource utilization. Conservation coupled with sustainable utilization is a crucial factor that can lead to the development of green economy surveillance competency at the community level. 2. Quality Check of Training Models and Curricula: The quality assessment of the training models and curricula by experts was found to be at a high. 3. Development of Prototype Innovators and Volunteers: Using knowledge from biodiversity as a foundation enhanced the community’s potential in terms of skills, awareness, tool utilization, and collaboration. This resulted in the surveillance system being more sustainable and yielding concrete results at the local level. 4. Development of Participatory Network Management: This helped the community create a strong network mechanism, utilize shared data for appropriate decision-making, and work together to drive the green economy sustainably.